6=x4.5

Simple and best practice solution for 6=x4.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=x4.5 equation:



6=x4.5
We move all terms to the left:
6-(x4.5)=0
We add all the numbers together, and all the variables
-(+x4.5)+6=0
We get rid of parentheses
-x4.5+6=0
We move all terms containing x to the left, all other terms to the right
-x4.5=-6
x=-6/1
x=-6

See similar equations:

| 40x+18x-3=368 | | 2x+49=5x+10 | | 104+t=t | | z+13=3z-13 | | 3x-19=6(x-3) | | 14a=2a-6 | | -5.6c-19.46=12.96+5.28-3c | | -3x=-4.5 | | 38-x=44 | | 36^x=6^x-8 | | 2(-5+m)=-20 | | I=5+i-2*1-2i+3i*i | | Z=5+i-2*1-2i+3i*i | | 36x=6x-8 | | 35=3g-5 | | 16+20m=5m-16+19m | | -x/2+10=12 | | 81-m=90 | | 73=13+4s | | 40+x=135 | | 3(w+58)=-84 | | -20-8y=18-10y | | 4−y=1 | | 2c-4=c+20 | | -1/5x+2=12 | | -2+4q=14 | | -10p=-11p+10 | | 4+m*9=7m | | 36x2-9x=0 | | -4x3=32 | | 4j+10=-9-j-1 | | (x–16)=–6 |

Equations solver categories